COMPARTILHAMENTO DO CONHECIMENTO: Um estudo sobre as práticas e iniciativas do processo de compartilhamento de uma Instituição de Ensino Superior (IES) - KONAKA, CARLOS TAKASHI (2019)
This research aims to understand how knowledge management and sharing can be used to improve the performance and work quality of faculty and managers of a Higher Education Institution (HEI) in São Bernardo do Campo, Brazil. As knowledge is one of the intangible assets of high value for the management of modern organizations, it becomes a differential in the creation of competitive advantage by institutions, especially nowadays, when the current economic crisis acts directly on the survival of universities and HEI. Thus, it was presented the main theoretical aspects related to knowledge management, knowledge sharing and HEI management demonstrated in the theoretical foundation. The methodology used for the elaboration of this work was the qualitative research, using the case study method, through individual and face-to-face semi-structured interviews, which took place in June and July 2019. Three coordinators of the Methodist University of São Paulo were interviewed. Through the analysis of the responses, it was found that the knowledge sharing program called "Atualizo 3.0" promoted by the principals and deans is the moment when all campuses come together and exchange information about teaching techniques and methods that can be used in the classroom. Despite this, there was a shortage in computer systems that would help to use the knowledge of those involved, and a lack of interest in the participation of some members, but even so, everyone who participated in the “Atualizo 3.0” program always comes out satisfied and with new ideas to improve their works in the classroom. Thus, it is observed in practice that having a knowledge sharing and management program facilitates the engagement for HEI management.